TGF-β–induced Phosphorylation of Smad3 Regulates Its Interaction with Coactivator p300/CREB-binding Protein - Shen, Xing (The American Society for Cell Biology, 1998)
Smads are intermediate effector proteins that transduce the TGF-β signal from the plasma membrane to the nucleus, where they participate in transactivation of downstream target genes. We have shown previously that coactivators p300/CREB-binding protein are involved in TGF-β–mediated transactivation of two Cdk inhibitor genes, p21 and p15. Here we examined the possibility that Smads function to regulate transcription by directly interacting with p300/CREB-binding protein. We show that Smad3 can interact with a C-terminal fragment of p300 in a temporal and phosphorylation-dependent manner. TGF-β–mediated phosphorylation of Smad3 potentiates the association between Smad3 and p300, likely because of an induced conformational change that removes the autoinhibitory interaction between the N- and C-terminal domains of Smad3. Consistent with a role for p300 in the transcription regulation of multiple genes, overexpression of a Smad3 C-terminal fragment causes a general squelching effect on multiple TGF-β–responsive reporter constructs. The adenoviral oncoprotein E1A can partially block Smad-dependent transcriptional activation by directly competing for binding to p300. Taken together, these findings define a new role for phosphorylation of Smad3: in addition to facilitating complex formation with Smad4 and promoting nuclear translocation, the phosphorylation-induced conformational change of Smad3 modulates its interaction with coactivators, leading to transcriptional regulation.